Cascading structural failures of towers in an electric power transmission line due to straight line winds - Dikshit, Saransh; Dobson, Ian; Alipour, Alice (Reliability engineering & system safety, 2024)
The bulk electricity that powers our society flows along high voltage transmission lines that are conducting cables hung with insulators from a series of transmission towers. High winds can damage these structures and the loss of the transmission line sometimes causes a blackout. When a tower structurally fails, the adjacent towers have unbalanced load, and are more likely to fail, so there is a cascading effect by which tower failures can lead to further tower failures. This paper analyzes the cascading failures of towers due to extreme straight line winds. A dynamic analysis of the transmission tower–insulator–conductor system under wind loads yields fragility curves that describe the probability of structural failure for both intact and failed adjacent towers. The paper then derives novel mathematical formulas for the probabilities of the number of towers that fail. The new formulas apply generally to cascading failure along a line of general components. The calculations use generating functions and computer algebra, and account for the interspersed anchor towers that are strongly built to withstand high winds. The effect of cascading on the number of towers failed and the life cycle cost is quantified in a case study of a transmission line with twenty-five towers. •Formulates probabilistic cascading structural failure of towers in a transmission line.•New mathematical formulas for the probability distribution of the number of towers failed.•Formulas apply generally to cascading along a line of general components.•State of the art dynamic analysis gives tower fragility curves under high wind loads.•Case study quantifies the effects and risk of cascading in a line of 25 towers. [Display omitted]